Influência do estádio reprodutivo do trigo na infecção de Fusarium graminearum s. str. e na contaminação dos grãos por desoxinivalenol - Bavia, Guilherme Passerini (2016)
In Southern Brazil, scab wheat or Fusarium Head Blight (FHB) is caused by up to five species of the Fusarium graminearum species complex, from which F. graminearum sensu stricto-type DON/15-ADON is the predominant species. The objective of this study was to analyze the influence of wheat?s reproductive stage on F. graminearum s.str. infection and DON contamination in wheat grains in susceptible cultivar and moderately susceptible cultivar to Fusarium Head Blight (FHB) and, additionally, to analyze the effect of the preventive fungicide application in the control of FHB and DON reduction in wheat grains. The inoculum consisted of a suspension of macroconidia (5x104 spores/ml) and the inoculation was done at growth stage 65 (anthesis half-way), growth stage 73 (early milk), and growth stage 83 (early dough). After inoculation, plants were maintained in continuous leaf wetting for 48h at 25ºC in growth chamber and then were transferred to greenhouse. Evaluation of incidence and severity was carried out seven days after the inoculation; the evaluation of Fusarium Damaged Kernels (FDK) was obtained after harvest and DON analysis by UPLC procedure. The experimental design was completely randomized and conducted in factorial scheme: 2 (cultivars) x 2 (with or without of fungicide) x 3 (inoculation times). The plant infection by F. graminearum s. str. is influenced by wheat?s phenological stage. Severity was higher with inoculation at the anthesis half-way stage than at the early grain milk stage. At the grain mass stage, inoculation induced a very low severity level (<1%). The early milk grain stage had higher DON accumulation than the other reproductive stages. Campeiro and CD105, moderately susceptible and susceptible, respectively, have a wide window of vulnerability to F. graminearum s. str. infection, but they differ in relation to the intensity of FHB and DON concentration. The cultivar Campeiro shows greater resistance to the disease and lower DON accumulation during its development. The preventive spray of fungicide tebuconazole reduced effectively the intensity of FHB and DON accumulation in wheat grains in both cultivars in all stages. Fungicide spray at the early grain mass stage suggests being a potentially critical moment for the control of DON in wheat grains